A case study on the effects of the wind catcher and Taiko-shoji in Japanese environment-friendly house. Issue 1 (2nd January 2019) - Endo, Tomoyuki; Otsuka, Masayuki; Minami, Yusuke; Umeno, Tetsuya
ABSTRACT: Recently, people around the world have actively made efforts to conserve energy in residential homes as a countermeasure against global warming. The awareness of the importance of energy saving has continued to grow in Japan since the Great East Japan Earthquake in March 2011. The interest in cross-ventilation for air conditioning energy saving in summer is especially increasing. Japan's climate features high temperatures and humidity, and it is a country in which people used cross-ventilation in their homes during summer and the middle season earlier. However, due to changes in modern society, including the progress in air-conditioning facilities, the focus on an environmentally conscious house design was lost. Therefore, studies about cross-ventilation have not been conducted in recent years. This study reconsidered the value of Japanese traditional houses and evaluated the effect of the planar-shaped house in cross-ventilation. It also surveyed the heat-insulating effect of a Taiko-shoji that was developed from an ordinary shoji screen used in Japanese traditional houses. The results show that a skylight opening increased the cross-ventilation air volume and that the shape worked effectively as a wind catcher without any special equipment. Moreover, the study found that the installment of a Taiko-shoji had a significant effect on heat insulation in summer and winter.